دور مبادئ أخلاقيات الأعمال في تحسين الأداء الوظيفي لدى الأساتذة الجامعيين دراسة ميدانية لعينة من المؤسسات الجامعية: The role of business ethics principles in improving the job performance of university professorsA field study of a sample of university institutions - خلف الله بن يوسف; نجلاء عبد المنعم إبراهيم (Journal of North African Economies, 2025)
The study aims to highlight the role of business ethics principles in improving the job performance of university professors, where the descriptive approach was used in the theoretical aspect to address concepts about business ethics and job performance in general, while the practical aspect was used the analytical approach, where the field study was to design A questionnaire and its distribution to the study sample, in order to reveal the relationship between the study variables and to present the optimal model for it. Among the most important findings of the study are the following: The variables of business ethics principles (transparency, honesty, responsibility, perfection, ) affect the job performance of university professors at the level of significant significance (α 0.05). There are correlative relationships between the business ethics variables (transparency, honesty, responsibility, perfection, ) and the job performance of university professors at the level of significance (α ≥ 0.05)..